Statistical Analyses of Learning Metrics in High School: a Study for Personalized Feedback Purposes - Moraes, Maely; Leitão, Gabriel; Melo, Áurea; Barreto, Raimundo (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2023)
Improving the teaching-learning process depends on the availability of useful information for decision-making. However, considering the sizeable increase in data generated by educational platforms, performing statistical analyses which can support proper pedagogical choices for teachers and personalized guidance for students has become a real challenge. This paper is in this context, where the main goal is understanding the data and learning metrics and identifying important information about the studied sample to support personalized feedback in a timely manner, in addition to subsequent quantitative analysis. Thus, this article presents an exploratory analysis of interaction data on an educational platform while applying preparatory simulations for the entrance exam in high school classes. The methodology adopted consisted of organizing and tabulating the data, generating information from graphs, calculating statistics on the variables of interest, and interpreting them. The results indicated the most relevant metrics to predict the student's situation at the end of the course besides the Traditional Score (TS). In addition, feedback examples were proposed based on the identified scenarios from the outcomes of the statistical analysis and learning metrics that aim to expand the evaluative elements beyond right and wrong.